The myth Iphigenia in Aulis: the violence in the ritual sacrifice of the parthenoi - Álvarez, Nazira (2018)
The objective of this paper is to focus on the presence of the symbolic violence hidden in the sacrificial ritual, in the myth of the tragedy Iphigenia at Aulis from Euripides. Human sacrifice is not an historical fact in Ancient Greece. Nevertheless, ritual sacrifice does appear as a motif in myth and literature. The analysis of the ritual immolation has a feminist literary critique approach, toward the presence of violence against women represented in the characters of the play, according to the individual and social dynamics of family and generational relations.